A Comparative Analysis of Control Methods Applied to Horizontal 2 DOF Robotic Arms - Giuliano A; Bone G; Gadsden SA; AlShabi M (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Robotic arm joint control is a well-explored field in the literature, given the need for accurate and robust path planning and execution for industrial robots. This paper explores various filtering control algorithms and compares their performance on a 2 degrees of freedom (DOF) horizontal robotic arm through an extensive simulation. The dynamics of a horizontal 2 DOF robot are outlined as well as the derivation of the models for the filters tested. The classic PID controller performance is used as the baseline and tested against the sliding mode control filter, sliding mode control filter with integral action, and Plestan sliding mode control filter. The performance of the various filters is benchmarked against combinations of variable payload, friction, noise, and saturation conditions.
Keywords: 40 Engineering; 46 Information and Computing Sciences; 4007 Control Engineering, Mechatronics and Robotics; 4602 Artificial Intelligence; 4010 Engineering Practice and Education